On chronology of the First Germanic Sound Shift (Lex Rask – Grimm) - Blažek, Václav (Lingua Posnaniensis, 2023)
This contribution analyzes the geographical name Θούλη, first recorded by Pytheas of Massalia in the period 330-325 BCE and mediated especially by Polybius, Strabo, Pliny and Procopius. Björn Collinder (1935/1936) designated this term as the earliest datable document of the Germanic Lautverschiebung. He also offered an appealing etymology, explaing the toponym on the basis of Old Norse þaularvágr “winding creek”, i.e. a place especially characteristic of the West Norwegian coast with its winding fjords. In the present study an alternative etymology by Torp is also analyzed, interpreting the toponym as a wooded place with regard to Old Norse þollr m. “tree, fir-tree, pine-tree”, and the witness of Procopius of Caesarea on the exceedingly large forests in Thule [‘The Gothic War’ VI.15]. Independently of whether either of the solutions of Collinder or Torp is correct, around 330 BCE the First Germanic Sound Shift should already have been operating.